Philosophical Foundations of Eminent Hong Kong Chinese CEOs’ Leadership - Cheung, Chau-kiu (Journal of business ethics, 2005)
Because of the importance of Confucian doctrines in shaping ethical business practices under Chinese leadership, revealing the roles of other Chinese ethical doctrines in modern Chinese leadership is informative. A thorough understanding of the ethical foundations of Chinese leadership is necessary for fruitful interaction with Chinese leaders, according to cultural fit theory. The present study illustrates the philosophical foundations of business management, based on dialogues with five eminent corporate executive officers (CEOs). It reveals that the CEOs practice a style of Chinese leadership synthesizing Confucian, Daoist, Mohist, and Legalist doctrines. The Confucian doctrines advocate benevolence, harmony, learning, loyalty, righteousness, and humility. They are the most prevalent tenets that support paternalism and collectivism. The Daoist doctrines emphasize flexibility and reversion (e.g., the principle that the weak can defeat the strong). They bolster the leader’s forbearance. The Mohist doctrines underpin thrift and working with the masses whereas the Legalist doctrines inculcate self-control and innovativeness. Hence, contemporary Chinese leadership does not rely exclusively on Confucian ethics and this reflects evolution over 1000s of years.